2014
DOI: 10.3109/0886022x.2014.882218
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen sulphide and tempol treatments improve the blood pressure and renal excretory responses in spontaneously hypertensive rats

Abstract: Oxidative stress and suppressed H 2 S production lead to increased renal vascular resistance, disturbed glomerular hemodynamics, and abnormal renal sodium and water handling, contribute to the pathogenesis and maintenance of essential hypertension in man and the spontaneously hypertensive rat. This study investigated the impact of H 2 S and tempol alone and in combination on blood pressure and renal hemodynamics and excretory functions in the SHR. Groups of WKY rats or SHR (n ¼ 6) were treated for 4 weeks eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 50 publications
2
29
1
Order By: Relevance
“…Many of the cardiovascular changes in the SHR are similar to those in hypertensive human subjects. Levels of H2S in plasma, urinary and gene expression and activity of CSE in thoracic aorta are all suppressed in SHR (Yan et al, 2004;Ahmad et al, 2014). A profound antihypertensive effect of H 2S in SHR has been identified by several groups.…”
Section: Role Of H 2 S In the Spontaneously Hypertensive Rat (Shr)mentioning
confidence: 97%
See 1 more Smart Citation
“…Many of the cardiovascular changes in the SHR are similar to those in hypertensive human subjects. Levels of H2S in plasma, urinary and gene expression and activity of CSE in thoracic aorta are all suppressed in SHR (Yan et al, 2004;Ahmad et al, 2014). A profound antihypertensive effect of H 2S in SHR has been identified by several groups.…”
Section: Role Of H 2 S In the Spontaneously Hypertensive Rat (Shr)mentioning
confidence: 97%
“…Additionally, in vivo studies have found that H2S acts as an antioxidant in the context of oxidative stress associated with hypoxic PHT and the mechanism appears to be partly through attenuating cellular content of oxidized glutathione (Wei et al, 2007). Treatment with NaHS decreases BP and oxidative stress in SHR, and combined NaHS and tempol therapy in SHR decreases BP to a greater extent (Ahmad et al, 2014). GYY4137 decreases superoxide generation in aorta of high-fat-fed apoE −/− mice, while CSE-knockout mice fed with atherogenic diet exhibit increased lesional oxidative stress Mani et al, 2013).…”
Section: Suppression Of Oxidative Stressmentioning
confidence: 99%
“…Also, renal function, as measured by creatinine clearance and urinary excretion of sodium, improved even more compared with single treatment. The improved anti-oxidant status is evidenced by increased total superoxide dismutase, total anti-oxidant capacity and NO, and decreased MDA levels in plasma [116].…”
Section: Hypertension-related Kidney Diseasementioning
confidence: 97%
“…A decreased CSE/H2S activity is a potential contributor to the pathogenesis of maternal hypertension in preeclampsia (Wang et al, 2013a). Also, the plasma H2S level and CSE protein expression in thoracic aorta are all suppressed in spontaneously hypertensive rats (SHR) in comparison with normotensive rats (Yan et al, 2004;Ahmad et al, 2014). An intriguing study has illustrated that the blood pressure is enhanced by treatment with the combination of CSE inhibitor DLpropargylglycine (PAG) or the CBS inhibitor aminooxyacetic acid (AOA) in rats, while either compound alone has no any effect on the arterial pressure, suggesting that H2S plays a critical role in regulating blood pressure (Roy et al, 2012).…”
Section: H 2 S-related Endothelial Dysfunction In Hypertensionmentioning
confidence: 99%